A detection algorithm for the first jump time in sample trajectories of jump-diffusions driven by α-stable white noise. Issue 19 (2nd October 2019) - Song, Jiao; Wu, Jiang-Lun
Abstract: The purpose of this paper is to develop a detection algorithm for the first jump point in sampling trajectories of jump-diffusions which are described as solutions of stochastic differential equations driven by α -stable white noise. This is done by a multivariate Lagrange interpolation approach. To this end, we utilize computer simulation algorithm in MATLAB to visualize the sampling trajectories of the jump-diffusions for various combinations of parameters arising in the modeling structure of stochastic differential equations.